Stimulation of Autotrophic Denitrification by Intrusions of the Bosporus Plume into the Anoxic Black Sea - Fuchsman, Clara A.; Murray, James W.; Staley, James T. (Frontiers in Microbiology, 2012)
Autotrophic denitrification was measured in the southwestern coastal Black Sea, where the Bosporus Plume injects oxidized chemical species (especially O2 and NO3-) into the oxic, suboxic and anoxic layers. Prominent oxygen intrusions caused an overlap of NOx- and sulfide at the same station where autotrophic denitrification activity was detected with incubation experiments. Several bacteria that have been proposed to oxidize sulfide in other low oxygen environments were found in the Black Sea including SUP05, Sulfurimonas, Arcobacter, and BS-GSO2. Comparison of TRFLP profiles from this mixing zone station and the Western Gyre (a station not affected by the Bosporus Plume) indicate the greatest relative abundance of Sulfurimonas and Arcobacter at the appropriate depths at the mixing zone station. The autotrophic gammaproteobacterium BS-GSO2 correlated with ammonium fluxes rather than with sulfide fluxes and the maximum in SUP05 peak height was shallower than the depths where autotrophic denitrification was detected. Notably, anammox activity was not detected at the mixing zone station, though low levels of DNA from the anammox bacteria Candidatus Scalindua were present. These results provide evidence for a modified ecosystem with different N2 production pathways in the southwest coastal region compared to that found in the rest of the Black Sea. Moreover, the same Sulfurimonas phylotype (BS139) was previously detected on >30 μm particles in the suboxic zone of the Western Gyre along with DNA of potential sulfate reducers, so it is possible that particle-attached autotrophic denitrification may be an overlooked N2 production pathway in the central Black Sea as well.